Chicago Paper - Effect of Time and Low Temperature on Physical Properties of Medium-carbon Steel (with Discussion) - G. A. Reinhardt; H. J. Cutler (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1920)
ThE Youngstown Sheet & Tube Co. has produced a large tonnage of 0.35 to 0.45 carbon forging steel, the acceptance of which was based on the physical properties of test specimens obtained by forging the original 5 3/4-in. (14.5 cm.) square bloom to a 3/4-in. (1.9 cm.) round. Annealed and tempered specimens were required. The test bars were annealed by heating from 900" to 950' C. and cooling slowly in mica. The test bars were tempered by heating to 825' to 875" C., quenching in water, and drawing to 515" to 535" C. Immediately after heat treatment, the test pieces were machined to a diameter of 0.534 in. (1.38 cm.) and tested. Very good physical properties were obtained and no difficulty was experienced in meeting the specifications called for. UlTimate Strength.. Elongation, Lb. pER Sq. In. PEE Cent.. in 4 In. Not LeEs Than Annealed specimens.............. 78,230 to 92,450. 18 Tempered...................... 120,000 to 149,350 9 After experience on this material, production of slightly higher carbon forging steel was started. The method of testing this material required that test blooms be either normalized or annealed. The normalizing consisted in heating to 850" to 900" C. and cooling in still air; the annealing, in heating to 850" to 900" C. and cooling in the furnace or in mica. From the treated bloom, the test pieces were taken either by core drilling or by sawing from points midway between the edges and the intersection of the diagonals. The cores or blocks were turned to a standard 2-in. test piece with a diameter of 0.564 in. and tested without further treatment. The physical requirements of the test pieces were: yield point, pounds per square inch minimum, 44,800; ultimate strength, pounds per square inch, 89,600 to 112,000; elongation, per cent. in 2 in. not less than 17. Difficulty was encountered as soon as work on this material was started. Many precautions and refinements were instituted but it was found very difficult to secure the required elongation.